Integration of International Legal Principles into the Indonesian National Legal System - Dadang Satria Wibawa; Dwi Imroatus Sholikah (IBLAM LAW REVIEW, 2026)
This study aims to analyze how principles of international law are integrated into Indonesia's national legal system—including the status of international principles, integration mechanisms (ratification, incorporation, transformation), as well as the challenges and implications. The method used is normative juridical with statute, conceptual, and historical approaches. The research results indicate that Indonesia has normatively accommodated the integration of international law principles; however, there are obstacles such as a status that is not yet fully automatic (dualistic), low regulatory harmonization, and resistance to external influence. It is recommended that the harmonization of national regulations with international obligations be strengthened, and that international law literacy within national institutions be improved.